Using social theory thinking through research - Pryke, Michael, 1955-; Rose, Gillian, 1962-; Whatmore, Sarah; Open University (London : SAGE, 2003)
As the authors demonstrate, research is not simply 'done', it's got to be thought about and thought through. 'Using Social Theory's' accessible style makes it suitable for anyone wishing to engage with ideas in research in the social sciences and humanities.
Published in association with the Open University.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research